2015
DOI: 10.1038/mi.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β in eosinophil-mediated small intestinal homeostasis and IgA production

Abstract: Eosinophils are multifunctional leukocytes that reside in the gastrointestinal (GI) lamina propria, where their basal function remains largely unexplored. In this study, by examining mice with a selective deficiency of systemic eosinophils (by lineage ablation) or GI eosinophils (eotaxin-1/2 double–deficient or CC chemokine receptor 3–deficient), we show that eosinophils support immunoglobulin A (IgA) class switching, maintain intestinal mucus secretions, affect intestinal microbial composition, and promote th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
191
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(204 citation statements)
references
References 58 publications
9
191
0
4
Order By: Relevance
“…For instance, although eosinophils release a plethora of proteins that are potent in killing worms in vitro, 177,178 eosinophils appear to be dispensable during most worm infections given that eosinophil-deficient mice are resistant seemingly despite their thinner mucus layer. 179 Mast cells on the other hand contribute to worm expulsion through the release of various proteases that serve to loosen tight junctions between epithelial cells, thus aiding in the shedding of embedded worms, notably during T. spiralis infection. [180][181][182] However, mast cells appear to be unessential for the expulsion of N. brasiliensis infection, [183][184][185] illustrating the context-specific nature of these responses.…”
Section: Expulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although eosinophils release a plethora of proteins that are potent in killing worms in vitro, 177,178 eosinophils appear to be dispensable during most worm infections given that eosinophil-deficient mice are resistant seemingly despite their thinner mucus layer. 179 Mast cells on the other hand contribute to worm expulsion through the release of various proteases that serve to loosen tight junctions between epithelial cells, thus aiding in the shedding of embedded worms, notably during T. spiralis infection. [180][181][182] However, mast cells appear to be unessential for the expulsion of N. brasiliensis infection, [183][184][185] illustrating the context-specific nature of these responses.…”
Section: Expulsionmentioning
confidence: 99%
“…Thus, despite being redundant for the expulsion of most nematodes, eosinophils might be important for wound healing and tissue regeneration in which they have been implicated in nonmucosal tissues. [194][195][196] Eosinophils have also been shown to promote the survival of long-lived plasma cells in the bone marrow 197 as well as the generation of IgA-secreting plasma cells in the gastrointestinal tract 179,198 (at least in the small intestine 199 ) via the production of IL-1b, suggesting that they might affect secondary challenge infections where antibodies presumably play a larger role. Indeed, both IL-5 and eosinophildeficient mice harbor increased numbers of N. brasiliensis larvae after secondary infection, 89 with similar results during secondary T. spiralis infection.…”
Section: Resolutionmentioning
confidence: 99%
“…The vast majority of these tissue-resident eosinophils (rEos) are found in the nonesophageal portions of the gastrointestinal tract, where they promote IgA class switching and the maintenance of IgA-expressing plasma cells (17,18). They also support the development of Peyer's patches and mucus production in the small intestine (18). rEos present in the adipose tissue produce IL-4, thereby favoring the polarization of adipose macrophages toward the alternatively activated phenotype (19).…”
Section: Cd101mentioning
confidence: 99%
“…iEos showed higher In fact, under baseline conditions, eosinophils rapidly leave the bloodstream to enter tissues, mainly the gastrointestinal tract, adipose tissue, thymus, uterus, and mammary glands, where they regulate a variety of important biological functions (1,2,8,16). The vast majority of these tissue-resident eosinophils (rEos) are found in the nonesophageal portions of the gastrointestinal tract, where they promote IgA class switching and the maintenance of IgA-expressing plasma cells (17,18). They also support the development of Peyer's patches and mucus production in the small intestine (18).…”
Section: Cd101mentioning
confidence: 99%
“…Yet, recent studies have shown that eosinophils also have a variety of homeostatic functions, including immunomodulation (3). For example, in the small intestine, which serves as the main reservoir for eosinophils at baseline, these cells have been shown to influence microbiotic content and mucus development and to be required for the production of secretory IgA, probably through production of IL-1β (4,5). In addition, eosinophils have been identified at substantial levels in white and brown adipose tissue, and compelling data establish the existence of a key eosinophil/macrophage axis in weight gain and adipose tissue homeostasis (6).…”
mentioning
confidence: 99%